Cell-autonomous roles of the ecdysoneless gene in Drosophila development and oogenesis - Gaziova, Ivana; Bonnette, Peter C; Henrich, Vincent C; Jindra, Marek (Development (Cambridge, England), 2004)
Steroid signaling underlies developmental processes in animals. Mutations that impair steroidogenesis in the fruit fly Drosophila melanogaster provide tools to dissect steroid hormone action genetically. The widely used temperature-sensitive mutation ecdysoneless(1) (ecd(1)) disrupts production of the steroid hormone ecdysone, and causes developmental and reproductive defects. These defects cannot be satisfactorily interpreted without analysis of the ecd gene. Here, we show that ecd encodes an as yet functionally undescribed protein that is conserved throughout eukaryotes. The ecd(1) conditional allele contains an amino acid substitution, whereas three non-conditional larval lethal mutations result in truncated Ecd proteins. Consistent with its role in steroid synthesis, Ecd is expressed in the ecdysone-producing larval ring gland. However, development of ecd-null early larval lethal mutants cannot be advanced by Ecd expression targeted to the ring gland or by hormone feeding. Cell-autonomous ecd function, suggested by these experiments, is evidenced by the inability of ecd(-) clones to survive within developing imaginal discs. Ecd is also expressed in the ovary, and is required in both the follicle cells and the germline for oocyte development. These defects, induced by the loss of ecd, provide the first direct evidence for a cell-autonomous function of this evolutionarily conserved protein.
Keywords: mutace; Animals; ovarium; Female; Oogenesis; sekvenční homologie aminokyselin; Sequence Homology, Amino Acid; Gene Expression Regulation, Developmental; oogeneze; ženské pohlaví; sekvence aminokyselin; endokrinní žlázy; Drosophila; Molecular Sequence Data; letální geny; Ecdysone; Mutation; Amino Acid Sequence; Endocrine Glands; molekulární sekvence - údaje; Drosophila Proteins; steroidy; Genes, Lethal; proteiny Drosophily; ekdyson; Larva; zvířata; vývojová regulace genové exprese; Steroids; Ovary; larva